Experimental Study Of Sheet Erosion On Slopes - Soon, Bobby (2002)
There is a need to determine a suitable Total Soil Loss Equation for the types of soil in and around the various Malaysian landscape. Currently there exists many methods, such as the linear equations and Revised Universal Soil Loss Equation (RULSE) that attempt to estimate the Soil Loss of a particular type of soil for different slope lengths, types of cover, rain intensity, slope gradient and kinetic energy of rain droplets. The objective of this study was to propose a method of estimating the Total Soil Loss for two particular types of soil at different ranges of slope gradient by observing the sheet erosion of the slope surface and utilising experimental method. The method employed are by simulating sheet erosion using artificial rainfall on sample plot in a controlled laboratory environment and attempting to observed trend of the results collected and correlate the results for different slope gradients. It was the aim of this project to establish a terminal gradient whereby soil erosions is kept to a minimum for the Malaysia landscape by controlling the gradient of the land.